(untitled) (Saptagandaki Journal, 2017)
This paper is an attempt to analyze the socio economic impact of food security program in the study area. Food security is widely defined as ‘access by all people at all times to enough food for an active healthy life’. Food insecurity is, therefore, the inability of a household or individual to meet required consumption levels in the face of fluctuating production, prices and incomes. Food insecurity is one of the major problems of the rural community. Community peoples are suffered from more food vulnerability due to the low production & having their traditional occupation as a way of livelihood. Their traditional occupation had faced different challenges due to modernization & globalization. Communities have been affected by the low production, lack of improved agriculture technology, road accessibility, and market facility and have experienced of rapid socio-economic, cultural changes over generation. Their way of earning livelihood differ by the development activities & these changes have been enumerated with case material from the survey. The Saptagandaki Journal Vol.8 2017: 56-68